2020
DOI: 10.1111/bcp.14245
|View full text |Cite
|
Sign up to set email alerts
|

Association between hydrochlorothiazide exposure and different incident skin, lip and oral cavity cancers: A series of population‐based nested case–control studies

Abstract: Hydrochlorothiazide-induced photosensitivity may increase squamous cell carcinoma (SCC), basal cell carcinoma (BCC) and lip cancer risk. The aim was to quantify these risks.Methods: Nested case-control studies using data from the UK THIN database from 01 January 1999 to 01 May 2016. Adults with incident SCC, BCC, melanoma, lip cancer and oral cancer were matched (on age, sex and calendar year of cohort entry) to controls using incidence density sampling. Incidence rate ratios (IRR) for each outcome were calcul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
37
4
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(54 citation statements)
references
References 25 publications
10
37
4
3
Order By: Relevance
“…In this population‐based study nested within Australia's most populous state, we found elevated risks of both lip cancer and malignant melanoma associated with HCTZ use. Our findings are in line with those reported from Denmark, 11,12 the UK, 10 and the United States, 13 and further support the existence of an association between HCTZ use and increased risks of skin cancer. This association is particularly relevant in Australia, as it is home to the highest incidence of skin cancer in the world and the use of HCTZ is widespread.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…In this population‐based study nested within Australia's most populous state, we found elevated risks of both lip cancer and malignant melanoma associated with HCTZ use. Our findings are in line with those reported from Denmark, 11,12 the UK, 10 and the United States, 13 and further support the existence of an association between HCTZ use and increased risks of skin cancer. This association is particularly relevant in Australia, as it is home to the highest incidence of skin cancer in the world and the use of HCTZ is widespread.…”
Section: Discussionsupporting
confidence: 92%
“…Most SCC diagnoses are not recorded in the NSWCR, and the only reportable SCC diagnosis for which we had sufficient numbers to examine was SCC of the lip. Still, we observed a small number of lip cancer cases, and while our risk estimates are similar to those reported in previous studies, 10,12,13 our findings should be interpreted with this limitation in mind. The cancer diagnosis data we used in our study go back as far as 1972, but our dispensing records began in 2004.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations